1993
DOI: 10.1055/s-2007-1021183
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Indices of Erythropoietin Administration in Athletes

Abstract: Recombinant human erythropoietin (EPO), commercially available since 1988, is thought to be used by athletes in aerobic sports for the purpose of increasing oxygen transport and aerobic power. In an attempt to identify EPO administration, we have studied the peripheral blood of 20 subjects practising sports at an amateur level. Automated cytometry was performed on the blood samples before and during 45 days of EPO treatment. The same hematological indices were determined for a control population that consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 2 publications
0
40
0
5
Order By: Relevance
“…Studies in athletes [26,27,28] have shown that erythropoietin administration increases work capacity, presumably by increasing the Hb concentration and thereby oxygen transport. Correction of anemia has been shown to improve QoL [29,30,31] and to reduce patient-reported fatigue [32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in athletes [26,27,28] have shown that erythropoietin administration increases work capacity, presumably by increasing the Hb concentration and thereby oxygen transport. Correction of anemia has been shown to improve QoL [29,30,31] and to reduce patient-reported fatigue [32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the dose (200 u kg−1) and the bioavail- 48,49]. However, after a single dose, Hb and Ht did not increase in spite of an increase in the numbers of ability of rHuEpo, a linear pharmacokinetic model was used to fit the data.…”
Section: Discussionmentioning
confidence: 99%
“…114 The subcutaneous administration of rhEpo (ϳ 200 U/kg per week) and oral iron (270 mg/day) for 30 days produced an increase in Hct from 42.7 to 50.8, as well as in sTfR (from 3.1-6.3 mg/L) and the ratio between sTfR and ferritin (from 3.2-11.8). 13 Casoni et al 115 administered rhEpo subcutaneously at doses of 30 U/kg body weight every other day for 30-45 days to 20 subjects practicing sports at an amateur level. rhEpo treatment was accompanied by twice weekly administration of parenteral iron (62 mg intravenously) and oral vitamins.…”
Section: Rbc Parameters Associated With Esa Dopingmentioning
confidence: 99%